Performativity Power Relations: A Discourse Analysis of Regent Sudewo’s Policies via the Instagram Account @wargapati_: A Discourse Analysis of Regent Sudewo’s Policies via the Instagram Account @wargapati_ - Lalu Didik Apriawan Lalu (Metafora: Education, Social Sciences and Humanities Journal, 2025)
Abstract This study examines the performativity of power relations within the social movement of Pati citizens through a critical discourse analysis of content posted on the Instagram account @wargapati_, in response to the policies of Regent Sudewo. Employing Norman Fairclough’s critical discourse analysis framework, the research investigates how textual, discursive, and social practices intersect to construct citizen representation, digital resistance, and the articulation of collective identity among the people of Pati. The data analyzed in this study consist of visual posts, captions, and digital interactions collected during the pivotal period of the social movement on August 13, 2025. The findings reveal that @wargapati_ serves not only as a space for free expression but also as a performative arena where citizens negotiate their position in relation to the local government of Pati Regency. Through visual, narrative, and affective strategies, the account reflects tensions between governmental policies and citizen aspirations, while simultaneously fostering a form of digital solidarity that is both disruptive and transformative. This research underscores the significance of social media—particularly Instagram—as a site of political articulation for Pati citizens and advocates for more participatory approaches in understanding the dynamics of power relations and resistance in the digital age Keywords: Social Movement, Power Relations, Discourse and Digital